Translucent γ-AlOOH and γ-Al2O3 glass-ceramics using the cold sintering process. (15th March 2021) - Hérisson de Beauvoir, Thomas; Estournès, Claude
Abstract: Cold Sintering Process has been applied to hydroxide precursors Al(OH)3, xH2 O to promote in situ reactive sintering. The application of sintering temperatures < 400°C led to the release of OH groups and partial crystallization into boehmite γ-AlOOH. This latter step is accompanied by a densification stage leading to the production of dense translucent pellet. From skeletal density measurements, it appears that not all the pellet is composed of crystalline phase, but contains a mix of amorphous and crystalline phase. The presence of amorphous phase seems to favor the mechanical stability of the samples made of the intermediate boehmite phase, which is brittle due to its oriented layer structure. Further heat treatment in an oven at 500°C induces the transformation of boehmite into γ-Al2 O3 . Here we demonstrate the possibility to produce optically translucent ceramics of low temperature stability gamma alumina structure. Graphical abstract: Image, graphical abstract